(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The research documented the environmental educational experience with young people, the interaction with the natural environment and the kingdom of fungi. Environmental education contributed to the recognition of space, life and dialogue with nature, principles linked to this research. Perceptions and knowledge in adolescents about the nature of rural communities of San Pedro Tlalcuapan, are a reflection of identity at the social and cultural level. The study was located in the qualitative narrative paradigm, environmental education workshops were developed in a focus group of 26 high school students responding to triggering questions about the environment, the ecology of wild mushrooms; uses and knowledge. Through the field diary, the information was analyzed in three constructs: uses and knowledge of wild fungi and the importance of these organisms in daily life. The research showed, gastronomic preparations of mushrooms in rural life, the group identified that mushrooms are a natural asset, stigmatized by “civilized” communities, also, they are ancestral inheritance. It was concluded, the focus group gave answers about ethnomicological knowledge and the relationship that these resources have in rural communities relatively isolated from cities and anthropocentric concessions, it is environmental education that revealed the interrelation network: community and the conservation of customs.